2021
DOI: 10.1063/5.0062032
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical characterizations of micro-LEDs grown on lower defect density epitaxial layers

Abstract: We have fabricated μLEDs of mesa sizes 10 × 10 and 15 × 15 μm2 on native (2021¯) semipolar substrates and on epitaxial lateral overgrown (ELO) wings of the (2021¯) substrate. The ELO μLEDs exhibited very low leakage current (less than 10−10 A) under forward bias (V < 2 V) and at reverse bias voltages, which was a reduction in several orders of magnitude when compared with planar μLEDs under the same fabrication and sidewall passivation scheme. Electrical characterization revealed that the mesa sidewall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The electrical, optical, and thermal characteristics of μLEDs mainly depend on the epitaxial materials, device pixel geometry, and packaging. Zhang et al comprehensively investigated the performance of μLEDs according to different shapes, sizes, and some drastic conditions. They concluded that the geometric shape of the device influences the current uniformity.…”
Section: Overview Of μLedsmentioning
confidence: 99%
“…The electrical, optical, and thermal characteristics of μLEDs mainly depend on the epitaxial materials, device pixel geometry, and packaging. Zhang et al comprehensively investigated the performance of μLEDs according to different shapes, sizes, and some drastic conditions. They concluded that the geometric shape of the device influences the current uniformity.…”
Section: Overview Of μLedsmentioning
confidence: 99%
“…However, high substrate cost, supply, and size limitations preclude the full realization of the market potential of semi-and non-polar LDs. To address these limitations, we propose a new approach combining ELO and a robust peeling method for semi-and non-polar optical devices ( [21][22][23][24][25][26][27][28], patent applications (i)-(xxx)). The feasibility of this new approach was studied for various devices such as non-polar LDs [21], n-side-distributed Bragg reflectors [23], and semipolar µLEDs [24].…”
Section: Introductionmentioning
confidence: 99%
“…To address these limitations, we propose a new approach combining ELO and a robust peeling method for semi-and non-polar optical devices ( [21][22][23][24][25][26][27][28], patent applications (i)-(xxx)). The feasibility of this new approach was studied for various devices such as non-polar LDs [21], n-side-distributed Bragg reflectors [23], and semipolar µLEDs [24]. Briefly, the process by which we may lower the commercialization hurdle consists of (1) utilizing ELO on expensive, free-standing GaN substrates for optical device fabrication, (2) removing the devices from the substrate, and (3) reusing the expensive substrate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations